2019
DOI: 10.1186/s12917-019-2111-6
|View full text |Cite
|
Sign up to set email alerts
|

Widespread co-endemicity of Trypanosoma species infecting cattle in the Sudano-Sahelian and Guinea Savannah zones of Cameroon

Abstract: Background African animal trypanosomosis remains the major constraint of livestock production and livelihood of pastoral communities in Cameroon. Despite several decades of vector and parasite control efforts, it has not been eradicated. Alternative and sustainable control strategies require a sound knowledge of the local species, strains and vectors. In the Sudano-Sahelian and Guinea Savannah of Cameroon the prevalence and genetic diversity of trypanosomes infecting cattle was investigated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 36 publications
9
24
1
Order By: Relevance
“…cosmopolitan blood parasites of ruminants which are known to in ict diseases were detected in Namchi, but only supported by a very low number of Blastn alignments [Additional le 1 Table S1]. Still, the presence of such organisms in our samples is in line with a recent epizootiological survey in the same indigenous Cameroonian cattle breeds that revealed nearly 90% of animals carried tickborne bacterial, piroplasmid and protozoan pathogens [18,19].…”
Section: Resultssupporting
confidence: 72%
“…cosmopolitan blood parasites of ruminants which are known to in ict diseases were detected in Namchi, but only supported by a very low number of Blastn alignments [Additional le 1 Table S1]. Still, the presence of such organisms in our samples is in line with a recent epizootiological survey in the same indigenous Cameroonian cattle breeds that revealed nearly 90% of animals carried tickborne bacterial, piroplasmid and protozoan pathogens [18,19].…”
Section: Resultssupporting
confidence: 72%
“…At even lower rates also Babesia spp., a blood-borne parasite known to cause Texas fever in cattle and Theileria spp., a cosmopolitan blood parasite of cattle and blood-invading bacteria of the Anaplasma genus were also detected in Namchi (Doayo) [see Supplement file 5 Table Supplemental S1]. Although these finding are only supported by a very low number of alignments of assembled contigs to the blastn database, this data is still in line with a recent epizootiological survey in the same indigenous Cameroonian cattle breeds which revealed that nearly 90% of animals were 8 infected with tick-borne bacterial, piroplasmid and protozoan pathogens [24,25].…”
Section: De Novo Assembly and Analysis Of Unmapped Genomic Sequence Rsupporting
confidence: 72%
“…The data used for this paper was obtained from the project "Pathogen detection in African cattle Breeds" Abanda et al, [24] and Paguem et al, [25].…”
Section: Sampling Library Construction and Sequencingmentioning
confidence: 99%
“…cosmopolitan blood parasites of ruminants which are known to inflict diseases were detected in Namchi, but only supported by a very low number of Blastn alignments [Additional file 1 Table S1]. Still, the presence of such organisms in our samples is in line with a recent epizootiological survey in the same indigenous Cameroonian cattle breeds that revealed nearly 90% of animals carried tick-borne bacterial, piroplasmid and protozoan pathogens [18,19].…”
Section: Whole Genome Sequencing Analysissupporting
confidence: 70%
“…The data used for this paper was obtained from the project "Pathogen detection in African cattle Breeds" Abanda et al [18] and Paguem et al [19].…”
Section: Sampling Library Construction and Sequencingmentioning
confidence: 99%